مراجعة علمية لنماذج من كتب النحاة المتأخرين والمحدثين: Shortcomings, Grammar Rules, Grammar Books, Redrafting - Dollah, Hanafi; Salim, Adel Ali (Al-Ḍād Journal, 2019)
This paper discusses the shortcomings of grammatical rules in Arabic grammar and writing that involved the authors and the reviewers. The shortcomings were found in the Arabic grammar books for the specialists at the university level, and they did not pay attention to them.This research dealt with these shortcomings by classifying them into categories in attempt to rephrase some of the grammatical rules in order to make it more specific and more comprehensive, two qualities that it need. The study benefited from the descriptive approach in mentioning the grammatical rules as stated from its sources. The analytical method was used in the discussion of the rule to clarify the shortcomings and the requirements of this rule. Next, this study cited the Holy Quran and the poetic poems to reduce these shortcomings to proof the need of modification. This study was committed to reach it objective and conclusion.